Airborne Lidar Measurements of Anthropogenic Methane Sources with CHARM-F during the CoMet 2.0 Arctic Campaign - Fruck, Christian; Quatrevalet, Mathieu; Wolff, Sebastian; Wirth, Martin; Kiemle, Christoph; Ehret, Gerhard; Fix, Andreas (2024)
The airborne Integrated Path Differential Absorption Lidar CHARM-F for accurate column concentration measurements of CH4 and CO2 has been very successfully deployed on a HALO aircraft campaign over Canada in late summer 2022. The scientific target areas, apart from natural sources (wetlands and thawing permafrost areas), included a variety of anthropogenic sources (oil and gas industry, coal mining, landfills and power plants). Using selected examples, we show the capabilities, but also the challenges, of trying to quantify methane fluxes from such measurements.